Many-body dispersion interactions for periodic systems based on maximally localized Wannier functions: Application to graphene/water systems - Partovi-Azar, Pouya; Kühne, Thomas D. (physica status solidi (b), 2016)
We extend the method of Silvestrelli [P. L. Silvestrelli, J. Chem. Phys. 139, 054106 (2013)] to approximate long-range van der Waals interactions at the density functional level of theory to periodic systems. The eventual approach is based on a combination of maximally localized Wannier functions with the quantum harmonic oscillator-model. Applying this scheme to study London dispersion forces between graphene and water layers, we find that collective many-body effects beyond simple pair-wise additive interactions are essential to accurately describe van der Waals forces.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Density functional theory; Graphene; Van der Waals forces; Wannier functions; Water